1995
DOI: 10.1182/blood.v86.2.744.bloodjournal862744
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of antisense oligodeoxynucleotide structure for targeting bcr-abl mRNA

Abstract: Antisense oligodeoxynucleotides targeted to bcr-abl are potential ex vivo purging agents for use with autologous bone marrow transplantation in the treatment of chronic myeloid leukemia (CML). We investigated, in a cell-free system, the activity and nuclease resistance of phosphodiester, phosphorothioate, chimeric methylphosphonate/phosphodiester, and chimeric methylphosphonate/phosphorothioate antisense octadecamers directed against either b2a2 or b3a2 bcr-abl breakpoint RNAs. Certain chimeric compounds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…376 Phosphorothioate ASODNs have a sulphur for oxygen substitution in the phosphate backbone of the DNA leading to higher nuclease resistance but also to a higher toxicity as well as aspecific interactions. 374,381 Methylphosphonate ASODNs are not charged thus generating less aspecific interactions. The poor solubility of these ASODNs, however, makes delivery via liposomes or phosphodiester tailing necessary.…”
Section: In Vitro Purgingmentioning
confidence: 99%
“…376 Phosphorothioate ASODNs have a sulphur for oxygen substitution in the phosphate backbone of the DNA leading to higher nuclease resistance but also to a higher toxicity as well as aspecific interactions. 374,381 Methylphosphonate ASODNs are not charged thus generating less aspecific interactions. The poor solubility of these ASODNs, however, makes delivery via liposomes or phosphodiester tailing necessary.…”
Section: In Vitro Purgingmentioning
confidence: 99%
“…AONs were originally designed to inhibit gene expression through steric inhibition of the translation machinery but have evolved into several parallel regulatory approaches. These include targeted degradation of mRNA through RNaseH activity [5], as well as alteration of mRNA splicing patterns by limiting the accessibility of specific splice sites [6]. RNA interference (RNAi) methods then followed, again evolving from the general notion of double stranded RNA being able to silence a complementary target mRNA [7], to the design of synthetic short interfering RNA (siRNA) [8], Dicer substrate siRNA (DsiRNA) [9], and other related constructs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Antisense strategies include the use of antisense oligodeoxynucleotides (ASODNs), antisense RNAs and ribozymes. ASODNs or expression vectors containing genes or gene fragments in the antisense orientation have been successfully developed for this purpose 6–8. Our previous study demonstrated that both antisense and siRNA approaches targeting the intracellular region of human EGFR could inhibit EGFR expression, thus exerting a suppressive effect on both U251 and C6 glioma cell growth in vitro and in vivo 5…”
Section: Introductionmentioning
confidence: 99%